Electrode for electricity storage device, and method for producing composite material for active material layer
By using composite materials containing active substances, carbon nanotubes and CMC as active substance layers in the power storage device, the problem of uneven thickness of the edge portion of the active substance layer is solved, and the stability and energy density of the electrode are improved.
Patent Information
- Application Number
- CN202380066843.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-22
- Filing Date
- 2023-08-30
- Publication Date
- 2025-04-25
AI Technical Summary
In the conventional power storage device, uneven thickness of the edge portions of the positive electrode and negative electrode active material layers leads to unstable shape of the active material layer, which may lead to overcompression or damage of the active material layer.
A composite material containing active substances that can absorb and release charge carriers, carbon nanotubes and CMC derived from carboxymethylcellulose ammonium are used as the active substance layer. The thickness and shape of the main body and edge portion of the active substance layer are controlled through specific mixing and processing methods.
It effectively suppresses the increase in edge ends of the active material layer and the collapse of the edge, improves the stability and energy density of the electrode, and avoids overcompression and damage of the active material layer.
Smart Images

Figure CN119895582A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a method for producing an electrode for a power storage device and a composite material for an active material layer. Background Art
[0002] Patent document 1 discloses a bipolar structured storage device formed by stacking a plurality of separately manufactured storage cells in series. The storage cell includes a positive electrode and a negative electrode as electrodes, and a separator disposed between the positive electrode and the negative electrode. The positive electrode includes a positive electrode active material layer in the central portion of one side of a positive electrode collector as a current collector. The positive electrode includes an uncoated portion other than the central portion of one side of the positive electrode collector. The uncoated portion is a frame-shaped portion surrounding the positive electrode active material layer. The negative electrode includes a negative electrode active material layer in the central portion of one side of a negative electrode collector as a current collector. The negative electrode includes an uncoated portion other than the central portion of one side of the negative electrode collector. The uncoated portion is a frame-shaped portion surrounding the negative electrode active material layer. The positive electrode active material layer and the negative electrode active material layer are opposite to each other via a separator.
[0003] The storage unit has a sealing portion disposed between the positive electrode and the negative electrode. The sealing portion is in a frame shape. The sealing portion is disposed between the uncoated portion of the positive electrode collector and the uncoated portion of the negative electrode collector. The sealing portion is a shape that surrounds the outer periphery of the positive electrode active material layer and the negative electrode active material layer. The sealing portion maintains the interval between the positive electrode collector and the negative electrode collector to prevent a short circuit between the collectors, and seals the positive electrode collector and the negative electrode collector in a liquid-tight manner.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2017-16825 Summary of the invention
[0007] Problem that the invention aims to solve
[0008] The edge of the positive electrode active material layer is sometimes thicker than the portion other than the edge of the positive electrode active material layer. In this case, in the power storage device, the amount of active material in the edge of the positive electrode active material layer is greater than the predetermined amount. In addition, the edge of the negative electrode active material layer is sometimes thicker than the portion other than the edge of the negative electrode active material layer. In this case, when the negative electrode active material layer is compressed to manufacture the negative electrode, the edge of the negative electrode active material layer may be damaged.
[0009] In addition, the edge of the positive electrode active material layer sometimes collapses. In this case, the size of the positive electrode active material layer in a planar shape will be larger than a preset size. Since the entire surface of the positive electrode active material layer is opposite to the negative electrode active material layer, the size of the negative electrode active material layer in a planar shape will also become larger. In addition, the edge of the negative electrode active material layer sometimes collapses. In this case, the size of the negative electrode active material layer in a planar shape will be larger than a preset size. Therefore, it is necessary to suppress the occurrence of adverse conditions caused by the shapes of the edges of the positive electrode active material layer and the negative electrode active material layer.
[0010] Solutions for solving problems
[0011] In one embodiment of the present disclosure, an electrode for a power storage device is provided. The electrode for a power storage device comprises: an active material layer, which is provided on the surface of a current collector; and an uncoated portion, which is provided on the surface of the current collector other than the portion on which the active material layer is provided, and surrounds the active material layer. The active material layer comprises: a main body; and an edge portion, which surrounds the main body and is located between the main body and the uncoated portion. The thickness of the main body is 100 μm or more and 400 μm or less. The active material layer contains: an active material capable of absorbing and releasing charge carriers; carbon nanotubes; and CMC derived from ammonium carboxymethylcellulose (NH4-CMC). The content of the CMC derived from ammonium carboxymethylcellulose (NH4-CMC) in the active material layer is 0.3 mass % or more and 0.6 mass % or less. The content of the carbon nanotubes in the active material layer is 0.005 mass % or more and 0.08 mass % or less. The maximum value of the thickness of the edge portion is 104% of the thickness of the main body. When the electrode is viewed in a plan view along the thickness direction of the active material layer, the maximum value of the dimension of the edge portion from the boundary between the main body portion and the edge portion to the front end of the edge portion is 5 mm.
[0012] In another embodiment of the present disclosure, a method for manufacturing a composite material for an active material layer used in manufacturing an electrode for a power storage device is provided. The electrode for a power storage device comprises: an active material layer, which is provided on the surface of a current collector; and an uncoated portion, which is provided on the surface of the current collector other than the portion on which the active material layer is provided, and surrounds the active material layer. The active material layer comprises: a main body; and an edge portion, which surrounds the main body and is located between the main body and the uncoated portion. The manufacturing method comprises: a first step of preparing a primary material by mixing a powder of an active material capable of absorbing and releasing charge carriers with a powder of ammonium carboxymethylcellulose (NH4-CMC); a second step of preparing a secondary material by mixing a solvent containing water and carbon nanotubes in the primary material; and a third step of preparing a composite material by mixing an aqueous binder in the secondary material and kneading. When the maximum value of the viscosity of the secondary material is set as the initial viscosity, in the third step, the composite material is kneaded until the viscosity of the composite material becomes less than 1 / 3 of the initial viscosity. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 is a cross-sectional view showing an electrode according to an embodiment.
[0014] Figure 2 It is a cross-sectional view showing an enlarged edge of the active material layer.
[0015] Figure 3 It is a top view showing an electrode according to an embodiment.
[0016] Figure 4 is a cross-sectional view showing a power storage device.
[0017] Figure 5 is a diagram schematically showing a coating device.
[0018] Figure 6 This is a diagram for explaining thixotropy. DETAILED DESCRIPTION
[0019] Below, according to Figure 1 to Figure 6 An embodiment of a method for concretely manufacturing an electrode for a power storage device and a composite material for an active material layer will be described.
[0020] <Electrode>
[0021] The electrode is used as a positive electrode or a negative electrode of a power storage device. The power storage device is, for example, a secondary battery such as a nickel-hydrogen secondary battery or a lithium-ion secondary battery. In addition, the power storage device may also be an electric double layer capacitor. The following describes the case of an electrode of a lithium-ion secondary battery.
[0022] like Figure 1 and Figure 2 As shown, the electrode 10 includes: a current collector 11; an active material layer 12 provided on a first surface 11a of the current collector 11; and an uncoated portion 11c provided outside the portion of the first surface 11a of the current collector 11 provided with the active material layer 12. In the following description, viewing the electrode 10 along the thickness direction of the active material layer 12 is referred to as a top view.
[0023] <Current Collector>
[0024] The current collector 11 is a chemically inert electrical conductor used to allow current to continue to flow through the active material layer 12 during the discharge or charge period of the lithium ion secondary battery. The current collector 11 is, for example, in the form of a foil. The current collector 11 is in the shape of a rectangular when viewed from above. The thickness of the foil-shaped current collector 11 is, for example, not less than 1 μm and not more than 100 μm. The thickness of the current collector 11 is preferably not less than 10 μm and not more than 60 μm. As the material constituting the current collector 11, for example, a metal material, a conductive resin material, a conductive inorganic material, etc. can be used. The current collector 11 is formed by Figure 5 The long strip-shaped current collector material 111 shown is formed by cutting at regular intervals in the longitudinal direction of the current collector 11 .
[0025] Examples of the metal material include copper, aluminum, nickel, titanium, and stainless steel. Examples of the conductive resin material include conductive polymer materials or resins obtained by adding conductive fillers to non-conductive polymer materials as needed.
[0026] In the case of the electrode 10 used as a positive electrode of an electric storage device, the current collector 11 is preferably an aluminum current collector composed of aluminum. The aluminum current collector may be composed of a single substance of aluminum or an aluminum alloy. Examples of aluminum alloys include Al-Mn alloys, Al-Mg alloys, and Al-Mg-Si alloys.
[0027] A carbon coating C is provided on the entire surface of the first surface 11a of the collector 11. The thickness of the carbon coating C is, for example, not less than 0.1 μm and not more than 5 μm. The carbon coating C is not particularly limited, and a known carbon coating used in the collector of the electrode can be applied. The carbon coating C can be formed, for example, by applying a carbon paste containing carbon particles and a binding material to the first surface 11a of the collector 11 and then curing the film of the applied carbon paste. The carbon coating C improves the hydrophilicity compared to the first surface 11a of the collector 11 itself. Therefore, a carbon coating C containing carbon particles and a binding material is provided on the first surface 11a of the collector 11.
[0028] <Active material layer>
[0029] The active material layer 12 is formed by drying and solidifying the composite material applied to the current collector material 111. The composite material will be described in detail later.
[0030] like Figure 2 and Figure 3 As shown, the active material layer 12 is formed on the carbon coating C in the first surface 11a of the current collector 11. When viewed from above, the active material layer 12 is in the shape of a long quadrilateral. Here, the current collector 11 is described. The current collector 11 has an uncoated portion 11c surrounding the active material layer 12. The uncoated portion 11c is arranged outside the portion of the first surface 11a of the current collector 11 where the active material layer 12 is arranged. When viewed from above, the uncoated portion 11c is in the shape of a long quadrilateral. The uncoated portion 11c has a portion where the active material layer 12 is sandwiched from both sides in the long side direction and a portion where the active material layer 12 is sandwiched from both sides in the short side direction.
[0031] The active material layer 12 includes a main body 12a in a rectangular shape and an edge 12b. The edge 12b surrounds the main body 12a and is located between the main body 12a and the uncoated portion 11c. The thickness t of the main body 12a is substantially constant at any location along the first surface 11a. The thickness t of the main body 12a can also be said to be the thickness of the active material layer 12.
[0032] The boundary between the main body 12a and the edge 12b is set to M, and the boundary between the first surface 11a and the edge 12b is set to N. The boundary N is located at the front end of the edge 12b. The edge 12b is a shape that tilts downward from the boundary M toward the boundary N, or a shape that tilts downward toward the boundary N after the thickness becomes slightly thicker relative to the main body 12a. In the case where the edge 12b is slightly thicker relative to the main body 12a, the maximum value of the thickness ta at the edge 12b is 104% of the thickness t of the main body 12a. Therefore, in the active material layer 12, the occurrence of the thickness ta of the edge 12b becoming thicker than the predetermined value at the end is suppressed. In addition, the predetermined value refers to 104% of the maximum value of the thickness t of the main body 12a. In addition, when viewed from above, the maximum value of the dimension L from the boundary M to the boundary N is 5mm. Therefore, in the active material layer 12, the occurrence of the edge collapse caused by the dimension L of the edge 12b becoming longer than the specified value is suppressed. In addition, the specified value refers to 5mm.
[0033] The active material layer 12 contains: an active material capable of absorbing and releasing charge carriers such as lithium ions; an aqueous binder; carboxymethyl cellulose derived from ammonium carboxymethyl cellulose; and carbon nanotubes. Hereinafter, ammonium carboxymethyl cellulose is described as "NH4-CMC". In addition, carboxymethyl cellulose derived from NH4-CMC is described as "CMC derived from NH4-CMC". In addition, carbon nanotubes are described as "CNT".
[0034] In the case of the electrode 10 used as the positive electrode of the power storage device, the active material contained in the active material layer 12 is a positive electrode active material. As the positive electrode active material, it is sufficient to use a material that can be used as a positive electrode active material for a lithium ion secondary battery, such as a lithium composite metal oxide with a layered rock salt structure, a metal oxide with a spinel structure, a polyanion compound, etc. In addition, two or more positive electrode active materials can also be used in combination. As a specific example of the positive electrode active material, olivine-type lithium iron phosphate (LiFePO4) as a polyanion compound can be cited.
[0035] In the case of the electrode 10 used as the negative electrode of the power storage device, the active material contained in the active material layer 12 is a negative electrode active material. As the negative electrode active material, any material that can be used as a negative electrode active material for a lithium ion secondary battery, such as lithium (Li) or carbon, a metal compound, an element that can be alloyed with lithium, or a compound thereof, can be used. As carbon, for example, natural graphite, artificial graphite, or hard carbon (difficult to graphitize carbon) or soft carbon (easy to graphitize carbon) can be listed. As artificial graphite, for example, highly oriented graphite, mesophase carbon microbeads, etc. can be listed. As elements that can be alloyed with lithium, for example, silicon and tin can be listed.
[0036] The content of the active material in active material layer 12 is not particularly limited. The content of the active material in active material layer 12 is, for example, 94 mass % or more, preferably 95 mass % or more. The content of the active material in active material layer 12 is, for example, 99.5 mass % or less, preferably 98.5 mass % or less.
[0037] The aqueous binder is a binder that can be dissolved in an aqueous solvent or dispersed in an aqueous solvent. The aqueous binder is a binder that is used by mixing with an active material in a state of being dispersed or dissolved in an aqueous solvent. The aqueous binder is not particularly limited, and as the aqueous binder contained in the active material layer of the lithium-ion secondary battery, previously known materials can be used. As aqueous binders, for example, fluorine-containing resins such as polyvinylidene fluoride, polytetrafluoroethylene, fluororubber, thermoplastic resins such as polypropylene and polyethylene, imide resins such as polyimide and polyamide-imide, alkoxysilyl-containing resins, acrylic resins such as poly(meth)acrylic acid, styrene-butadiene rubber, sodium alginate, ammonium alginate, water-soluble cellulose ester crosslinked products, starch-acrylic acid graft polymers can be listed. The aqueous binder contained in the active material layer 12 can be one or more.
[0038] The content of the aqueous binder in active material layer 12 is not particularly limited. The content of the aqueous binder in active material layer 12 is, for example, 0.5 mass % or more, preferably 1 mass % or more. In addition, active material layer 12 preferably contains styrene-butadiene rubber as the aqueous binder.
[0039] CMC derived from NH4-CMC is generated when all or part of ammonia (NH3) in NH4-CMC is released when the composite material containing NH4-CMC is dried. When all ammonia (NH3) in NH4-CMC is released, the generated CMC derived from NH4-CMC becomes H-CMC. When part of ammonia (NH3) in NH4-CMC is released, NH4-CMC and H-CMC coexist in the generated CMC derived from NH4-CMC.
[0040] The degree of etherification of CMC derived from NH4-CMC is preferably greater than 0.5 and less than 0.65. The content of CMC derived from NH4-CMC in the active material layer 12 is greater than 0.3% by mass and less than 0.6% by mass, preferably greater than 0.35% by mass and less than 0.5% by mass. In addition, the content of CMC derived from NH4-CMC in the active material layer 12 means the total content of NH4-CMC and H-CMC. When the entire amount of ammonia (NH3) in NH4-CMC is detached when the composite material is dried, the total content of NH4-CMC and H-CMC means the total amount of H-CMC.
[0041] When the content of CMC derived from NH4-CMC is less than 0.3% by mass, poor dispersion of the composite material forming the active material layer 12 will occur, which is not preferred. On the other hand, when the content of CMC derived from NH4-CMC exceeds 0.6% by mass, the flexibility of the active material layer 12 is reduced, and cracks in the electrode 10 are easily generated, so it is not preferred. Therefore, by setting the content of CMC derived from NH4-CMC to the above range, the occurrence of the edge 12b of the active material layer 12 being higher can be suppressed, and the occurrence of damage during compression of the active material layer 12 can be suppressed. In addition, by setting the content of CMC derived from NH4-CMC to the above range, the peel strength of the active material layer 12 relative to the collector 11 is improved.
[0042] CNT can be a multi-layer carbon nanotube (MWCNT) or a single-layer carbon nanotube (SWCNT). These CNTs can be used alone or in combination of two or more. The fiber length and fiber diameter of CNT are not particularly limited. The fiber length of CNT is, for example, 1 μm or more and 50 μm or less, preferably 3 μm or more and 30 μm or less. The fiber diameter of CNT is, for example, 1 nm or more and 5 μm or less, preferably 1.1 nm or more and 3 μm or less, and more preferably 1.2 nm or more and 2 μm or less. In this embodiment, SWCNT is used.
[0043] The content of CNT in the active material layer 12 is 0.005 mass % or more and 0.08 mass % or less, preferably 0.008 mass % or more and 0.06 mass % or less, and more preferably 0.01 mass % or more and 0.05 mass % or less. By setting the content of CNT to the above range, the loss of thixotropy of the composite material forming the active material layer 12 can be suppressed. "Thixotropy" refers to the following properties: it originally looks like a solid, but when shear stress such as mixing or shaking is continuously applied, the viscosity decreases and becomes liquid, and on the other hand, when the stress is removed, the viscosity gradually recovers and returns to the original state. Such a property is called thixotropy.
[0044] The active material layer 12 can contain other components other than the above-mentioned active material, aqueous binder, CNT, and CMC derived from NH4-CMC as needed. As other components, for example, conductive aids, electrolytes (polymer matrix, ion conductive polymer, electrolyte, etc.), and electrolyte support salts (lithium salts) for improving ion conductivity can be listed. As conductive aids, for example, acetylene black, carbon black, and graphite can be listed. The types and contents of other components are not particularly limited, and can be appropriately referred to the previously known insights about lithium ion secondary batteries.
[0045] From the viewpoint of increasing the energy density of the power storage device, the active material layer 12 is formed thicker than usual. When the power storage device is used as a vehicle-mounted power source, especially when the power storage device is used as a power source for an electric vehicle, a high-capacity power storage device such as 50 kWh is required. Therefore, the thickness of the active material layer 12 becomes larger. The thickness t of the main body 12a in the active material layer 12 is greater than 100 μm and less than 400 μm.
[0046] The density of the active material layer 12 is not particularly limited. The density of the active material layer 12 is, for example, 1.0 g / cm 3 When the density of the active material layer 12 is high, the long-term output of the power storage device is likely to decrease due to the inclusion of CNTs. The density of the active material layer 12 is, for example, 3.0 g / cm 3 the following.
[0047] The weight per unit area of the active material layer 12 is not particularly limited, and can be appropriately referred to the conventionally known viewpoints on lithium-ion secondary batteries. However, from the viewpoint of increasing the energy density of the storage cell 20, it is preferable to increase the weight per unit area of the active material layer 12. The weight per unit area of the positive electrode active material layer 21b is, for example, 55 mg / cm 2 Above and 90mg / cm 2 Below, preferably 60 mg / cm 2 More preferably 70 mg / cm 2The weight per unit area of the negative electrode active material layer 22 b is, for example, 25 mg / cm 2 Above and 45mg / cm 2 Below, preferably 30 mg / cm 2 above.
[0048] <Electricity storage device>
[0049] Next, an example of a power storage device to which the electrode 10 is applied will be described.
[0050] The power storage device to which the electrode 10 is applied is, for example, a power storage module used as a power source for various vehicles such as a forklift, a hybrid car, and an electric car. In the present embodiment, a case where the power storage device is a lithium ion secondary battery is exemplified.
[0051] like Figure 4 As shown, the power storage device 100 includes a unit stack 30 in which a plurality of power storage cells 20 are stacked in a stacking direction. Hereinafter, the stacking direction of the plurality of power storage cells 20 is referred to as the stacking direction. The power storage cell 20 includes a positive electrode 21, a negative electrode 22, a separator 23, and a spacer 24. Either or both of the positive electrode 21 and the negative electrode 22 of the power storage cell 20 are the above-mentioned electrodes 10. Figure 4 In the figure, the illustration of the carbon coating C and the detailed illustration of the edge 12b are omitted.
[0052] The positive electrode 21 includes a positive electrode current collector 21a and a positive electrode active material layer 21b provided on a first surface 21a1 of the positive electrode current collector 21a. When the positive electrode 21 is the electrode 10, the positive electrode current collector 21a is the current collector 11. The positive electrode active material layer 21b is the active material layer 12.
[0053] The positive electrode active material layer 21b is formed in the central portion of the first surface 21a1 of the positive electrode collector 21a in a plan view. The peripheral portion of the first surface 21a1 of the positive electrode collector 21a in a plan view is a positive electrode uncoated portion 21c where the positive electrode active material layer 21b is not provided. The positive electrode uncoated portion 21c is arranged so as to surround the positive electrode active material layer 21b in a plan view.
[0054] The negative electrode 22 includes a negative electrode current collector 22a and a negative electrode active material layer 22b provided on a first surface 22a1 of the negative electrode current collector 22a. When the negative electrode 22 is the electrode 10, the negative electrode current collector 22a is the current collector 11. The negative electrode active material layer 22b is the active material layer 12.
[0055] When viewed from above, the negative electrode active material layer 22b is formed in the central part of the first surface 22a1 of the negative electrode collector 22a. The peripheral edge of the first surface 22a1 of the negative electrode collector 22a when viewed from above is a negative electrode uncoated portion 22c where the negative electrode active material layer 22b is not provided. The negative electrode uncoated portion 22c is arranged in a manner surrounding the negative electrode active material layer 22b when viewed from above. The positive electrode 21 and the negative electrode 22 are arranged in a manner that the positive electrode active material layer 21b and the negative electrode active material layer 22b are opposite to each other in the stacking direction. That is, the relative direction of the positive electrode 21 and the negative electrode 22 is consistent with the stacking direction. The negative electrode active material layer 22b is formed to be one circle larger than the positive electrode active material layer 21b. When the negative electrode active material layer 22b is formed to be one circle larger than the positive electrode active material layer 21b, when viewed from above, the formation area of the positive electrode active material layer 21b is entirely located within the formation area of the negative electrode active material layer 22b.
[0056] The positive electrode current collector 21a has a second surface 21a2 which is a surface on the opposite side to the first surface 21a1. The positive electrode 21 is an electrode of a monopolar structure in which neither the positive electrode active material layer 21b nor the negative electrode active material layer 22b is formed on the second surface 21a2 of the positive electrode current collector 21a. The negative electrode current collector 22a has a second surface 22a2 which is a surface on the opposite side to the first surface 22a1. The negative electrode 22 is an electrode of a monopolar structure in which neither the positive electrode active material layer 21b nor the negative electrode active material layer 22b is formed on the second surface 22a2 of the negative electrode current collector 22a.
[0057] The separator 23 is a member disposed between the positive electrode 21 and the negative electrode 22 , and prevents a short circuit caused by contact between the positive electrode 21 and the negative electrode 22 by isolating the positive electrode 21 and the negative electrode 22 , while allowing charge carriers such as lithium ions to pass therethrough.
[0058] The separator 23 is, for example, a porous sheet or nonwoven fabric containing a polymer that absorbs and retains electrolytes. As materials constituting the separator 23, for example, polyolefins such as polypropylene and polyethylene, polyesters, etc. can be cited. The separator 23 can have a single-layer structure or a multi-layer structure. The multi-layer structure can have, for example, an adhesive layer, a ceramic layer as a heat-resistant layer, etc.
[0059] The separator 24 is disposed between the first surface 21a1 of the positive electrode collector 21a of the positive electrode 21 and the first surface 22a1 of the negative electrode collector 22a of the negative electrode 22, and is closer to the outer peripheral side than the positive electrode active material layer 21b and the negative electrode active material layer 22b. The separator 24 is bonded to both the positive electrode collector 21a and the negative electrode collector 22a. The separator 24 maintains the interval between the positive electrode collector 21a and the negative electrode collector 22a, prevents the short circuit between the positive electrode collector 21a and the negative electrode collector 22a, and seals the positive electrode collector 21a and the negative electrode collector 22a in a liquid-tight manner.
[0060] The spacer 24 extends along the peripheral edge of the positive electrode collector 21a and the negative electrode collector 22a in a plan view and is formed into a frame shape surrounding the positive electrode collector 21a and the negative electrode collector 22a. The spacer 24 is arranged between the positive electrode uncoated portion 21c of the first surface 21a1 of the positive electrode collector 21a and the negative electrode uncoated portion 22c of the first surface 22a1 of the negative electrode collector 22a.
[0061] Examples of the material constituting the spacer 24 include various resin materials such as polyethylene (PE), modified polyethylene (modified PE), polystyrene (PS), polypropylene (PP), modified polypropylene (modified PP), ABS resin, and AS resin.
[0062] A sealed space S surrounded by a frame-shaped separator 24 , the positive electrode 21 , and the negative electrode 22 is formed inside the power storage cell 20 . A separator 23 and an electrolyte are accommodated in the sealed space S. The peripheral edge of the separator 23 is buried in the separator 24 .
[0063] As the electrolyte, for example, a liquid electrolyte, a polymer gel electrolyte containing an electrolyte retained in a polymer matrix can be listed. As the liquid electrolyte, for example, a liquid electrolyte containing a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent can be listed. As the electrolyte salt, known lithium salts such as LiClO4, LiAsF6, LiPF6, LiBF4, LiCF3SO3, LiN(FSO2)2, and LiN(CF3SO2)2 can be used. In addition, as the non-aqueous solvent, known solvents such as cyclic carbonates, cyclic esters, chain carbonates, chain esters, and ethers can be used. In addition, two or more of these known solvent materials can also be used in combination.
[0064] The separator 24 can suppress leakage of the electrolyte contained in the sealed space S to the outside by sealing the sealed space S between the positive electrode 21 and the negative electrode 22. In addition, the separator 24 can suppress the intrusion of moisture from the outside of the power storage device 100 into the sealed space S. Moreover, the separator 24 can suppress the leakage of gas generated from the positive electrode 21 or the negative electrode 22 due to charge and discharge reactions, etc. to the outside of the power storage device 100. In order to arrange the separator 24 for performing the above functions between the positive electrode 21 and the negative electrode 22, the positive electrode 21 includes a positive electrode uncoated portion 21c, and the negative electrode 22 includes a negative electrode uncoated portion 22c.
[0065] The cell stack 30 has a structure in which a plurality of power storage cells 20 are stacked so that the second surface 21a2 of the positive electrode current collector 21a contacts the second surface 22a2 of the negative electrode current collector 22a. Thus, the plurality of power storage cells 20 constituting the cell stack 30 are connected in series.
[0066] Here, in the unit stack 30, two storage cells 20 adjacent in the stacking direction form a pseudo bipolar electrode 25 in which the positive electrode collector 21a and the negative electrode collector 22a in contact with each other are regarded as one collector. The pseudo bipolar electrode 25 includes a collector having a structure in which the positive electrode collector 21a and the negative electrode collector 22a are stacked, a positive electrode active material layer 21b formed on one side of the collector, and a negative electrode active material layer 22b formed on the other side of the collector.
[0067] In addition, the positive electrode collector 21a and the negative electrode collector 22a may also form a bipolar collector formed by joining the second surface 21a2 of the positive electrode collector 21a and the second surface 22a2 of the negative electrode collector 22a. In this case, the positive electrode 21 and the negative electrode 22 form a bipolar electrode 25 having a bipolar collector formed by joining the positive electrode collector 21a and the negative electrode collector 22a.
[0068] The power storage device 100 includes a pair of current-carrying bodies composed of a positive current-carrying plate 40 and a negative current-carrying plate 50 arranged in a stacking direction of the unit stack 30 so as to sandwich the unit stack 30. The positive current-carrying plate 40 and the negative current-carrying plate 50 are each composed of a material having excellent electrical conductivity.
[0069] The positive electrode current supply plate 40 is electrically connected to the second surface 21a2 of the positive electrode collector 21a of the positive electrode 21 disposed outermost at one end in the stacking direction. The negative electrode current supply plate 50 is electrically connected to the second surface 22a2 of the negative electrode collector 22a of the negative electrode 22 disposed outermost at the other end in the stacking direction.
[0070] The charging and discharging of the power storage device 100 is performed by terminals provided respectively on the positive electrode current supply plate 40 and the negative electrode current supply plate 50. As a material constituting the positive electrode current supply plate 40, for example, the same material as that constituting the positive electrode current collector 21a can be used. The positive electrode current supply plate 40 can also be composed of a metal plate thicker than the positive electrode current collector 21a used in the unit stack 30. As a material constituting the negative electrode current supply plate 50, for example, the same material as that constituting the negative electrode current collector 22a can be used. The negative electrode current supply plate 50 can also be composed of a metal plate thicker than the negative electrode current collector 22a used in the unit stack 30.
[0071] <Method for producing an electrode for a power storage device>
[0072] Next, a method for manufacturing the electrode 10 will be described.
[0073] The electrode 10 is manufactured by sequentially performing a composite material manufacturing step and an active material layer forming step.
[0074] <Composite material manufacturing process>
[0075] The method for manufacturing a composite material comprises: a first step of preparing a primary material by mixing a powdered active material with a powdered NH4-CMC; a second step of preparing a secondary material by mixing a solvent containing water and CNTs in the primary material; and a third step of preparing a slurry-like composite material by adding styrene-butadiene rubber to the secondary material and kneading the mixture. In the following description, styrene-butadiene rubber is referred to as [SBR].
[0076] When the total mass of the solid components contained in the composite material is set to 100 parts by mass, the content of the active material is preferably 94 parts by mass or more and 95 parts by mass or less. The mixing amount of NH4-CMC mixed in the first step is preferably 0.3 parts by mass or more and 0.6 parts by mass or less. The mixing method in the first step is not particularly limited as long as it is a method that can uniformly disperse the solid components contained in the primary material, and the previously known mixing method used in the mixing of the powder can be applied. As the above-mentioned mixing method, for example, mixing by manual stirring using a stirring rod, mixing by mechanical stirring using an ultrasonic disperser, etc. can be cited.
[0077] The second step is to prepare a secondary material by mixing a solvent containing water and CNTs into the above-mentioned primary material. CNTs are prepared in a paste state in advance. The secondary material is prepared by mixing a solvent containing water and CNTs in a primary material and kneading them. The maximum value of the viscosity of the secondary material in a slurry or capillary state into which the solvent has been put is set as the initial viscosity. The initial viscosity can be specified in the state after the third step. In addition, the solvent containing water is preferably a solvent with water as the main component, for example, a solvent in which the mass ratio of water in the solvent is 50 to 100 mass%. In the present embodiment, water is used as a solvent. Water is mixed into the composite material, for example, in such a way that the solid content of the composite material is 50 mass% and above and below 70 mass%.
[0078] The third step is to prepare a slurry-like composite material by adding SBR in the secondary material and mixing. SBR is pre-prepared into a paste. When the total mass of the solid components contained in the composite material is set to 100 mass parts, the content of CNT is preferably more than 0.005 mass parts and less than 0.08 mass parts. In addition, when the total mass of the solid components contained in the composite material is set to 100 mass parts, the content of SBR is preferably more than 1.0 mass parts and less than 5.0 mass parts.
[0079] The specific mixing method in the second step and the third step is not particularly limited as long as it is a method that can uniformly mix the components contained in the secondary material and the composite material, and can be applied to the previously known mixing method used in the manufacture of the composite material for the electrode of the secondary battery. As the above-mentioned mixing method, for example, mixing by manual stirring using a stirring rod, and mixing by mechanical stirring using a planetary mixer, a homogenizer, a homodisperser, a Henschel mixer, a Banbury mixer, a ribbon mixer, a V-type mixer, a rotation-revolution mixer, and a conventional mixer, an ultrasonic disperser, etc. can be cited.
[0080] In the third step, the composite material is preferably kneaded until the viscosity of the composite material becomes less than 1 / 3 of the initial viscosity, and particularly preferably, it is kneaded until it becomes less than 1 / 4. When the viscosity of the composite material is kneaded until it becomes less than 1 / 3 of the initial viscosity, the viscosity reduction of the composite material caused by kneading will stabilize and become a state suitable for coating.
[0081] <Active material layer forming step>
[0082] The active material layer forming step is performed by applying the composite material to the first surface 111a of the current collector material 111 and then drying the composite material coating layer. As described above, the current collector material 111 is in the form of a long strip. As a method for applying the composite material to the current collector material 111, a die coating method can be cited.
[0083] like Figure 5 As shown, the composite material 121 is applied to the current collector material 111 by a coating device 31. The coating device 31 includes a slit die 32, a support roll 33, a supply roll 34, and a tension roll 35.
[0084] The slit die 32 includes a reservoir 31a storing the composite material 121 and a discharge port 31b discharging the composite material 121 stored in the reservoir 31a. In the slit die 32, the composite material 121 stored in the reservoir 31a is pressure-fed by a pump (not shown). The composite material 121 pressure-fed by the pump is discharged from the discharge port 31b.
[0085] The support roller 33 is arranged at a position opposite to the ejection port 31b of the slit die 32. The support roller 33 is arranged to be movable relative to the slit die 32 to a coating position and a retreat position, wherein the coating position is a position where the composite material 121 can be coated on the first surface 111a of the collector material 111 through the slit die 32, and the retreat position is a position where the composite material 121 cannot be coated on the collector material 111 through the slit die 32.
[0086] The collector material 111 is wound around the supply roller 34. The collector material 111 fed from the supply roller 34 is supplied to the slit die 32. The tension roller 35 applies tension to the collector material 111 fed from the supply roller 34. Then, the composite material 121 ejected from the slit die 32 is coated on the first surface 111a of the collector material 111 by conveying the collector material 111 along the support roller 33 moved to the coating position. Thus, a coating layer of the composite material 121 is formed on the collector material 111.
[0087] The composite material 121 is ejected from the slit die 32 from both ends of the short side direction of the current collector material 111. Thus, uncoated portions 11c not coated with the composite material 121 are formed on both sides of the short side direction of the current collector material 111.
[0088] The composite material 121 is intermittently applied to the first surface 111a of the collector material 111 by ejecting and stopping the composite material 121 from the slit die 32 at respectively determined times. Since the composite material 121 is applied intermittently, the coating start end and coating end end of the composite material 121 are formed in the coating layer. The coating start end of the composite material 121 is formed at the first end in the long side direction of the active material layer 12 in the active material layer 12 formed by drying the coating layer. The coating end end of the composite material 121 is formed at the second end in the long side direction of the active material layer 12 in the active material layer 12 formed by drying the coating layer. The thickness of the coating layer of the composite material 121, the length or width in the long side direction are appropriately set according to the size of the lithium ion secondary battery.
[0089] In addition, by stopping the ejection of the composite material 121 from the slit die 32, an uncoated portion 11c not coated with the composite material 121 is formed between the adjacent coating layers in the long side direction of the collector material 111. When the ejection is stopped, the pressure applied to the slit die 32 is instantly reduced by a sack back mechanism (not shown), so that the ejection of the composite material 121 is instantly stopped. Therefore, the coating layer of the composite material 121 and the uncoated portion 11c are alternately formed in the long side direction of the collector material 111.
[0090] As a drying method for the coating layer of the composite material 121, for example, natural drying, low temperature wind, hot wind, vacuum, infrared, far infrared, electron beam, microwave, etc. can be listed. These drying methods can also be combined with two or more. The drying temperature is 20 degrees or more and 120 degrees or less, preferably 40 degrees or more and 100 degrees or less.
[0091] By drying the coating layer of the composite material 121 , NH 3 is released from NH 4 —CMC contained in the composite material 121 . Thus, CMC derived from NH 4 —CMC is mixed into the active material layer 12 .
[0092] Furthermore, in order to increase the electrode density, a compression step of compressing the active material layer 12 may be performed after the drying step. Examples of the compression method of the active material layer 12 include a roll pressing method, a die pressing method, and a calender press method. The pressing pressure is preferably 0.1 t / cm 2 Above and 10t / cm 2 Below, more preferably 0.5t / cm 2 Above and 5.0t / cm 2 the following.
[0093] The electrode 10 may be wound up in a roll shape at a certain timing between the coating step, the drying step, and the compression step, and at least after the compression step. In addition, the drying step may be performed again after the compression step. By performing these steps, the active material layer 12 is formed on the current collector material 111.
[0094] Then, the current collector material 111 on which the active material layers 12 are formed is cut at the uncoated portions 11 c between the active material layers 12 , thereby manufacturing the electrode 10 .
[0095] <Method for manufacturing power storage device>
[0096] A method for manufacturing the power storage device 100 will be described.
[0097] The power storage device 100 is manufactured by sequentially performing a power storage cell forming step and a cell stack forming step.
[0098] <Electricity Storage Cell Forming Process>
[0099] In the storage cell formation process, first, the positive electrode 21 and the negative electrode 22 are arranged so that the positive electrode active material layer 21b and the negative electrode active material layer 22b face each other in the stacking direction with the separator 23 sandwiched therebetween, and the separator 24 is arranged between the positive electrode 21 and the negative electrode 22 and between the positive electrode uncoated portion 21c and the negative electrode uncoated portion 22c. At this time, the edge 12b of the positive electrode active material layer 21b faces the negative electrode active material layer 22b via the separator 23. In addition, the edge 12b of the negative electrode active material layer 22b faces the separator 23.
[0100] After that, the positive electrode 21, the negative electrode 22, and the separator 23 are joined to the spacer 24 by welding to form an assembly in which each member is integrated. As a method for welding the spacer 24, for example, a known welding method such as heat welding, ultrasonic welding or infrared welding can be cited.
[0101] Next, an electrolyte is injected into the sealed space S in the assembly through an injection port provided in a portion of the separator 24 , and then the injection port is closed. Thus, the electricity storage cell 20 is formed.
[0102] <Unit stack forming step>
[0103] In the unit stack formation process, first, a plurality of storage cells 20 are stacked so that the second surface 21a2 of the positive electrode collector 21a faces the second surface 22a2 of the negative electrode collector 22a. At this time, the second surface 21a2 of the positive electrode collector 21a of one storage cell 20 and the second surface 22a2 of the negative electrode collector 22a of the other storage cell 20 are in contact with each other. Thereafter, the plurality of storage cells 20 are integrated by joining the outer peripheral portions of the spacers 24 in the storage cells 20 adjacent to each other in the stacking direction.
[0104] Next, the positive electrode current-carrying plate 40 is overlapped on the second surface 21a2 of the positive electrode collector 21a of the positive electrode 21 disposed at the outermost end in the stacking direction and fixed to the second surface 21a2 in an electrically connected state. Similarly, the negative electrode current-carrying plate 50 is overlapped on the second surface 22a2 of the negative electrode collector 22a disposed at the outermost end in the stacking direction and fixed to the second surface 22a2 in an electrically connected state. At this time, the second surface 22a2 of the negative electrode collector 22a and the negative electrode current-carrying plate 50 are brought into contact with each other. Thus, the power storage device 100 is formed.
[0105] <Effects of implementation methods>
[0106] Next, the operation of this embodiment will be described.
[0107] Active material layer 12 contains 0.3 mass % or more and 0.6 mass % or less of CMC derived from NH 4 —CMC. In addition, composite material 121 forming active material layer 12 contains NH 4 —CMC.
[0108] Figure 6 The solid line shows the relationship between the viscosity and shear stress of the composite material 121 containing 0.4 mass % NH4-CMC and 0.05 mass % SWCNT after kneading for 30 minutes. Figure 6 The double-dotted dashed line shows the relationship between the viscosity and shear stress of the composite material 121 after kneading the composite material 121 without SWCNT for 30 minutes. Figure 6 As shown, the viscosity in a state of low shear stress is maintained high compared to the case without SWCNT, and the thixotropy of the composite material 121 is improved. Due to the improvement of the thixotropy of the composite material 121, the viscosity of the composite material 121 is also improved compared to the case without NH4-CMC.
[0109] Therefore, the occurrence of end heightening is suppressed at the coating start end and coating end end of the coating layer formed by coating the composite material 121 on the collector material 111. As a result, in the active material layer 12 formed by drying the coating layer, the occurrence of end heightening is suppressed in the edge 12b formed by the coating start end and coating end end.
[0110] When the composite material 121 contains 0.05 mass % of SWCNT, the viscosity of the composite material 121 under a low shear stress state is improved. The inventors have found that when the composite material 121 contains NH4-CMC, Figure 6 As shown by the two-dot chain line, the thixotropy is lost by kneading the composite material 121.
[0111] Furthermore, the inventors have found that by including CNTs in the composite material 121 , loss of thixotropy is suppressed, and a decrease in the viscosity of the composite material 121 is suppressed, thereby turning the composite material 121 into a liquid state.
[0112] In this embodiment, the active material layer 12 contains SWCNTs as CNTs in an amount of 0.005 mass % or more and 0.08 mass % or less. That is, the composite material 121 forming the active material layer 12 also contains SWCNTs. Thus, in the coating layer formed by applying the composite material 121 to the collector material 111, the occurrence of edge collapse at the edge is suppressed. As a result, even in the active material layer 12 formed by drying the coating layer, the occurrence of edge collapse at the edge 12b is suppressed.
[0113] <Effects of implementation>
[0114] According to the above-described embodiment, the following effects can be obtained.
[0115] (1) In the power storage device electrode 10 , the content of CMC derived from NH 4 —CMC in the active material layer 12 is 0.3 mass % or more and 0.6 mass % or less. This prevents the edge 12 b of the active material layer 12 from becoming high.
[0116] In the positive electrode active material layer 21b of the positive electrode 21, the occurrence of the edge 12b being raised is suppressed. Therefore, in the power storage device 100, the amount of active material in the edge 12b of the positive electrode active material layer 21b is suppressed from becoming greater than a predetermined amount, and the edge 12b of the positive electrode active material layer 21b can be suppressed from being over-compressed by the amount of the end being raised when the positive electrode active material layer 21b is compressed. In addition, in the negative electrode active material layer 22b of the negative electrode 22, the occurrence of the edge 12b being raised is suppressed. Therefore, in the case where the negative electrode active material layer 22b is located on both sides of the negative electrode collector 22a, the edge 12b of the negative electrode active material layer 22b can be suppressed from being over-compressed by the amount of the end being raised when the negative electrode active material layer 22b is compressed. When the negative electrode active material layer 22b is located on one surface of the negative electrode current collector 22a and the positive electrode active material layer 21b is located on the other surface of the negative electrode current collector 22a, it is possible to prevent the edge 12b of the negative electrode active material layer 22b from being bent and damaged when the negative electrode active material layer 22b is compressed. In addition, in the power storage device 100, it is possible to prevent the edge 12b of the negative electrode active material layer 22b from piercing the separator 23.
[0117] The active material layer 12 contains 0.005 mass % or more and 0.08 mass % or less of CNTs. This can suppress the occurrence of edge collapse at the edge of the coating layer formed by applying the composite material 121 to the collector material 111. As a result, in the active material layer 12 formed by drying the coating layer, the occurrence of edge collapse at the edge 12b is suppressed.
[0118] Therefore, the size of the positive electrode active material layer 21b in the plane shape can be suppressed from becoming larger than the preset size. Since the entire surface of the positive electrode active material layer 21b is opposite to the negative electrode active material layer 22b, the size of the negative electrode active material layer 22b in the plane shape can be suppressed from becoming larger. In addition, the occurrence of edge collapse at the edge 12b of the negative electrode active material layer 22b is suppressed. The size of the negative electrode active material layer 22b in the plane shape can be suppressed from becoming larger than the preset size. As a result, the occurrence of adverse conditions caused by the shape of the edge 12b of the active material layer 12 can be suppressed.
[0119] (2) The carbon coating layer C is provided on the first surface 11 a of the current collector 11 . Furthermore, the active material layer 12 is formed on the carbon coating layer C. The carbon coating layer C improves the peel strength of the active material layer 12 with respect to the current collector 11 .
[0120] (3) CNT is a single-layer carbon nanotube. Since the fiber length of the single-layer carbon nanotube is longer than that of the multi-layer carbon nanotube, the thixotropy of the composite material 121 is easily improved. Therefore, the amount of CNT required to impart the desired thixotropy to the composite material 121 can be reduced. As a result, the amount of CNT required to suppress the collapse of the edge 12b of the active material layer 12 can be reduced.
[0121] In addition, the present embodiment can be implemented by being modified as follows. The present embodiment and the following modified examples can be implemented in combination with each other within the range that there is no technical contradiction.
[0122] The formation range of the carbon coating layer C on the first surface 11a of the current collector 11 may be changed. For example, the carbon coating layer C may be formed only on the range of the first surface 11a where the active material layer 12 is formed, or may be partially formed on a part of the range.
[0123] The electrode 10 may also be an electrode of a bipolar structure. The electrode 10 includes a bipolar current collector. The bipolar current collector is a laminate formed by bonding a foil-shaped positive electrode current collector and a foil-shaped negative electrode current collector in a thickness direction. Examples of the bipolar current collector include a current collector formed by bonding aluminum foils to each other and a current collector formed by bonding aluminum foil and copper foil.
[0124] The specific configuration of the power storage device 100 using the electrode 10 is not particularly limited as long as at least one positive electrode or at least one negative electrode corresponds to the configuration of the electrode 10. For example, the number of power storage cells 20 constituting the power storage device 100 may be one. In addition, the power storage device 100 may be provided with a restraining member that applies a restraining load to the unit stack 30 in the stacking direction. In addition, the power storage device 100 may be provided with an electrode 10 configured as a bipolar electrode.
[0125] Example
[0126] Hereinafter, examples in which the above-mentioned embodiment is further concretized will be described.
[0127] <Example 1 to Example 2>
[0128] <Production of positive electrode sheet>
[0129] A positive electrode composite material containing LiFePO4, ammonium carboxymethylcellulose (NH4-CMC), single-walled carbon nanotubes (SWCNTs) and styrene-butadiene rubber (SBR) with respective solid contents in the blending ratios shown in Table 1 was prepared.
[0130] First, as a first step, the full amount of LiFePO4 was mixed with the full amount of NH4-CMC to adjust the primary material. Then, as a second step, water and SWCNT were added to the primary material so that the solid content ratio of the composite material finally prepared was 83% by mass to prepare the secondary material. As a third step, the full amount of SBR was added to the secondary material to prepare the composite material. Then, as a third step, the composite material was mixed at 20 rpm using a planetary mixer for 5 hours to obtain a positive electrode composite material with a viscosity of less than 1 / 4 of the initial viscosity of the secondary material.
[0131] As the positive electrode collector 21a, a carbon-coated aluminum foil with a thickness of 30 μm was prepared. The positive electrode composite material was applied in a film-like manner to the surface of the positive electrode collector 21a provided with the carbon coating C using a die coating method to form a coating layer. The coating layer of the positive electrode composite material was heat-treated at 50°C, and after drying and curing, the coating layer of the positive electrode composite material was compressed. The positive electrode sheets of Examples 1 to 2 were prepared in which a positive electrode active material layer 21b with a thickness of 400 μm was formed on the positive electrode collector 21a.
[0132] [Table 1]
[0133]
[0134] <Comparative Example 1-Comparative Example 2>
[0135] As shown in Table 1, in Comparative Example 1, the mixing ratio of NH4-CMC in the positive electrode active material layer was set to 0.2 mass %. In Comparative Example 2, the CMC salt was changed to ammonium carboxymethylcellulose and the positive electrode active material layer was formed from a positive electrode composite material containing sodium carboxymethylcellulose.
[0136] <Example 3 to Example 5>
[0137] <Production of negative electrode sheet>
[0138] A negative electrode composite material comprising graphite, ammonium carboxymethyl cellulose (NH4-CMC), single-layer carbon nanotubes (SWCNT) and styrene-butadiene rubber (SBR) and having a solid content of each being a mixing ratio shown in Table 2 was prepared. First, as a first step, the full amount of graphite was mixed with the full amount of NH4-CMC to adjust the primary material. Then, as a second step, water and the full amount of SWCNT were added to the primary material so that the solid content ratio of the composite material finally prepared became 60% by mass to prepare a secondary material. As a third step, a composite material was prepared by adding the full amount of SBR to the secondary material. Then, as a third step, the composite material was mixed for 5 hours at 20rpm using a planetary mixer to obtain a negative electrode composite material having a viscosity of less than 1 / 4 of the initial viscosity of the secondary material.
[0139] As the negative electrode collector 22a, a carbon-coated copper foil with a thickness of 10 μm was prepared. The negative electrode composite material was applied in a film form to the surface of the negative electrode collector 22a provided with the carbon coating C using a die coating method to form a coating layer. The coating layer of the negative electrode composite material was heat-treated at 50°C, and after the negative electrode composite material was dried and cured, it was compressed. Negative electrode sheets of Examples 3 to 5 were prepared in which a negative electrode active material layer 22b with a thickness of 400 μm was formed on the negative electrode collector 22a.
[0140] [Table 2]
[0141]
[0142] <Comparative Examples 3 to 5>
[0143] As shown in Table 2, in Comparative Example 3, the mixing ratio of NH4-CMC in the negative electrode active material layer was set to 0.2% by mass. In Comparative Example 4, the CMC salt was changed to ammonium carboxymethylcellulose and the negative electrode active material layer was formed from a negative electrode composite material containing sodium carboxymethylcellulose. In Comparative Example 5, the negative electrode active material layer was formed from a negative electrode composite material not containing SWCNT.
[0144] <Measurement of the edge>
[0145] The thickness ta and the dimension L of the edge 12b of each active material layer 12 in Examples 1 to 5 and Comparative Examples 1 to 5 were measured. The case where the thickness ta of the edge 12b is 104% or less of the thickness t of the main body 12a is set as [○], and the case where the thickness ta of the edge 12b exceeds 104% of the thickness t of the main body 12a is set as [×]. In addition, when looking down at the active material layer 12, the case where the dimension L from the boundary M to the boundary N is 5 mm or less is set as [○], and the case where the dimension L exceeds 5 mm is set as [×]. The results are shown in Tables 1 and 2. In addition, in Tables 1 and 2, CMC salt is NH4-CMC or Na-CMC, and CMC represents NH4-CMC.
[0146] In Comparative Examples 1 and 3, when the mixing ratio of NH4-CMC was 0.2 mass %, the edge 12b collapsed when the coating layer of each composite material was dried and compressed after curing. It can be considered that the reason is that the composite material was poorly dispersed. In addition, in Comparative Examples 1 and 3, since the edge 12b collapsed, the measurement of the end heightening was not performed. On the other hand, as shown in Examples 1 to 2 and Examples 3 to 5, when the mixing ratio of NH4-CMC was 0.3 mass % or more and 0.6 mass % or less, the occurrence of the end heightening was suppressed.
[0147] In addition, when Na-CMC was used, the edge heightening occurred as shown in Comparative Examples 2 and 4. On the other hand, as shown in Examples 1 to 2 and Examples 3 to 5, the edge heightening was suppressed by using NH4-CMC.
[0148] These results show that, unlike the case of using Na-CMC, the inclusion of a predetermined amount of NH 4 -CMC can suppress the occurrence of high ends of edge portion 12 b in active material layer 12 formed by drying, solidifying and compressing the composite material.
[0149] On the other hand, it is shown that when the composite material contains NH4-CMC, the thixotropy is lost by kneading the composite material, but when the composite material contains SWCNT, the thixotropy is not lost. As a result, by containing a predetermined amount of SWCNT, as shown in Examples 1 to 2 and Examples 3 to 5, the occurrence of edge collapse at the edge 12b of the active material layer 12 is suppressed.
Claims
1. An electrode for a power storage device, comprising: an active material layer, which is arranged on the surface of a current collector; and an uncoated portion, which is arranged outside the portion of the surface of the current collector where the active material layer is arranged, surrounding the active material layer, the active material layer comprising: a main body; and an edge portion, which surrounds the main body and is located between the main body and the uncoated portion, the thickness of the main body is not less than 100 μm and not more than 400 μm, the electrode for a power storage device is characterized in that, The active material layer contains: an active material capable of absorbing and releasing charge carriers; carbon nanotubes; and CMC derived from ammonium carboxymethyl cellulose (NH4-CMC). The content of CMC derived from ammonium carboxymethylcellulose (NH4-CMC) in the active material layer is 0.3 mass % or more and 0.6 mass % or less, The content of the carbon nanotubes in the active material layer is 0.005 mass % or more and 0.08 mass % or less, The maximum value of the thickness of the edge portion is 104% of the thickness of the main body portion. When the electrode is viewed in a plan view along the thickness direction of the active material layer, the maximum value of the dimension of the edge portion from the boundary between the main body portion and the edge portion to the front end of the edge portion is 5 mm.
2. The electrode for a power storage device according to claim 1, wherein A carbon coating layer including carbon particles and a binding material is provided on the surface of the current collector, and the active material layer is formed on the carbon coating layer.
3. The electrode for a power storage device according to claim 1 or claim 2, wherein: The carbon nanotubes are single-walled carbon nanotubes.
4. A method for manufacturing a composite material for an active material layer, wherein the composite material for an active material layer is used to manufacture an electrode for a storage device, wherein the electrode for a storage device comprises: an active material layer, which is arranged on the surface of a collector; and an uncoated portion, which is arranged outside the portion of the surface of the collector where the active material layer is arranged, and surrounds the active material layer, wherein the active material layer comprises: a main body; and an edge portion, which surrounds the main body and is located between the main body and the uncoated portion. The method for producing the composite material for an active material layer is characterized by comprising: In the first step, a primary material is prepared by mixing a powder of an active substance capable of absorbing and releasing charge carriers with a powder of ammonium carboxymethylcellulose (NH4-CMC); A second step is to mix a solvent containing water and carbon nanotubes into the primary material to prepare a secondary material; and The third step is to prepare a composite material by mixing a water-based binder into the secondary material and kneading the mixture. When the maximum value of the viscosity of the secondary material is defined as the initial viscosity, the composite material is kneaded in the third step until the viscosity of the composite material becomes 1 / 3 or less of the initial viscosity.
Citation Information
Patent Citations
Secondary battery and method for manufacturing the same
JP2017016825A